Open study

is now brainly

With Brainly you can:

  • Get homework help from millions of students and moderators
  • Learn how to solve problems with step-by-step explanations
  • Share your knowledge and earn points by helping other students
  • Learn anywhere, anytime with the Brainly app!

A community for students.

Consider the polynomial P(x) = ax^4 - x^3 - 14x^2 + bx - 6 where a and b are constant. If one of the zeros of P(x) is 2 and the remainder is -36 when P(x) is devided by (x + 1). Find the values of a and b. How do I solve this?

I got my questions answered at in under 10 minutes. Go to now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly


Get your free account and access expert answers to this and thousands of other questions

it means P(2) = 0 and P(-1) = -36 now, aplly of them to P(x)
okay got the asnwers. thank you very much!
a=6, b=-13, right ?

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

wait no i got a=2 b=19 :-/
can you show me your calculation? i want to see where i did wrong
well, look this: P(x) = ax^4 - x^3 - 14x^2 + bx - 6 P(2) = 0, it means a(2)^4 - (2)^3 - 14(2)^2 + b(2) - 6 = 0 16a - 8 - 56 + 2b - 6 = 0 16a + 2b - 70 = 0 16a + 2b = 70 8a + b = 35 .......... (1st equation) then P(-1) = -36, means a(-1)^4 - (-1)^3 - 14(-1)^2 + b(-1) - 6 = 0 a + 1 - 14 - b - 6 = 0 a - b - 19 = 0 a - b = 19 ............ (2nd equation) solve for x and y, by using elimination and substitution method (1st) + (2nd), gives 9a = 54 (cancel out for b) a = 6 now, substitute a=6 to one of equation, let the (2nd eq) a-b=19 6 - b = 19 b = 6 - 19 = -13
why is the second equation is equal to 0 and not -36 since its the remainder?
i used remainder theorem, if P(x) divided by (x+a) so its remainder is P(-a)
shouldnt it be a(-1)^4 - (-1)^3 - 14(-1)^2 + b(-1) - 6 = -36 ?
opsss.. u are correct, sorry my bad because copy and paste from the1st equ... yeah, it should a(-1)^4 - (-1)^3 - 14(-1)^2 + b(-1) - 6 = -36 sorry, ur answer is right and mine was wrong
dont angry to me, yea :)
but when i cant seem to factorise it completely :-/ there's a remainder. is it correct? or is my calculation wrong? bcs the 2nd questions ask me to factorise it completely,
not at all :)
factor ? i think we didnt see and neednt factor there but elimination and substitution method
i dont understand
oh sorry, miss comunication (because my english soo bad :(, sorry again ) if u have pounded the value of a and b, just plug of them to P(x), from here we can find the factors of P(x)
so what i should do is devide 2x^4 - x^3 - 14x^2 + 19x - 6 with x^2 - x -2 rite? i tried calculating it but i end up with remainders. what should i do?
how come x^2-x-2 ? what is it
(x-2) and (x+1) is two of the four factors right? (x+1) is given. and x=2 is also given therefore x-2=0 correct? or am i wrong?
if the problem told u one of the zeros or one of the factor, yea right but wrong for (x+1), it's not a root because it has remainder
oh right i i should try to find the root by myself?
yea, u might use trial and error or use synthetic division to find the other factors
okay i get. thank you so much, again! you've been a great help :)
i have asked to wolfram, it said to me here :^4-x^3-14x^2%2B19x-6
you're welcome :)

Not the answer you are looking for?

Search for more explanations.

Ask your own question